Exploring single-use, multi-use dialysers for patient well-being - Nitiakaliyani, Balasubramaniam *; Sri Ameera, Abdul Rahim *; Ho, Sweet Lee * (Malaysiakini, 2024)
Dialysis treatment is a critical lifeline for patients with kidney failure. Patients need to decide the choice between single-use and multi-use dialysers. This plays a vital role in ensuring patient safety and treatment effectiveness.